Reliability Analysis of a 500 Wp Solar Power Plant System in Jalan Karya Wisata Residential Area - Alwiansyah (Bahasa Indonesia, 2026)
Solar Power Generation Systems (SPGS) are a renewable energy solution that is increasingly being implemented on a household scale, but technical constraints related to reliability often arise due to mismatches between electricity production and load. This study aims to analyze the performance and reliability of a 500 WP solar power system through a quantitative descriptive approach. The parameters evaluated include output power, system efficiency, and power availability for household loads. Measurement results show that the total installed power load reaches 1,150 Watts with a daily energy consumption of 5.12 kWh. Meanwhile, the PLTS system is only capable of producing an average of 2.5 kWh of energy per day, resulting in an energy deficit of 2.62 kWh per day. These findings indicate that the installed system is not yet capable of supplying the load independently and currently only functions as a support system to reduce PLN electricity consumption. Additional energy storage capacity of at least 4 to 5 battery units with a capacity of 100-120Ah is needed to maintain power stability at night. This capacity mismatch affects system reliability, accelerates battery component degradation, and reduces Mean Time Between Failure (MTBF). More selective load management and additional solar panel capacity are the main recommendations for improving the efficiency and technical life of this residential solar power system.